ADDICTIVE BEHAVIOR, A MENTAL INHABILITATION DISORDER - Sandí Esquivel, Luis Eduardo (2021)
As a result of misconceptions in scientific knowledge —as well as an approach based on prejudice and insufficient information— stigma, discrimination, rejection, aggression and abandonment have prevailed in the understanding of addictive behaviors in society— particularly in the health system. The aim of this article is to confirm the clinical and scientific bases behind addictive behaviors founded on clinical experience and scientific knowledge. For this purpose, a detailed scientific study was put together on the basis of an extensive clinical experience. The evidence compiled firmly shows that addictive disorders considerably compromise multiple neural circuits responsible for functions of the brain.